Fungal CSL transcription factors - Převorovský, Martin (BioMed Central, 2007)
BACKGROUND: The CSL (CBF1/RBP-Jκ/Suppressor of Hairless/LAG-1) transcription factor family members are well-known components of the transmembrane receptor Notch signaling pathway, which plays a critical role in metazoan development. They function as context-dependent activators or repressors of transcription of their responsive genes, the promoters of which harbor the GTG(G/A)GAA consensus elements. Recently, several studies described Notch-independent activities of the CSL proteins. RESULTS: We have identified putative CSL genes in several fungal species, showing that this family is not confined to metazoans. We have analyzed their sequence conservation and identified the presence of well-defined domains typical of genuine CSL proteins. Furthermore, we have shown that the candidate fungal protein sequences contain highly conserved regions known to be required for sequence-specific DNA binding in their metazoan counterparts. The phylogenetic analysis of the newly identified fungal CSL proteins revealed the existence of two distinct classes, both of which are present in all the species studied. CONCLUSION: Our findings support the evolutionary origin of the CSL transcription factor family in the last common ancestor of fungi and metazoans. We hypothesize that the ancestral CSL function involved DNA binding and Notch-independent regulation of transcription and that this function may still be shared, to a certain degree, by the present CSL family members from both fungi and metazoans.